ANALISIS TINDAK TUTUR DIREKTIF TOKOH JIRO HORIKOSHI DALAM FILM KAZE TACHINU - Gede Eka Dana Artama; Ladycia Sundayra (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2024)
This research aims to investigate the meaning of directive speech acts uttered by the character Jiro Horikoshi and describe the responses of interlocutors to the utterances made by the character Jiro Horikoshi in the film "Kaze Tachinu" ("The Wind Rises"). This research falls under qualitative descriptive research, and the source of data used consists of dialogues spoken by the characters in the film "Kaze Tachinu." The method employed in this research is observation and note-taking. The data collected is then analyzed using the theory of directive speech acts by Namatame and the theory of responses by Harvey and Smith. The results of this research include 37 instances of directive utterances, with details as follows: 15 instances of command (meirei), 12 instances of request (irai), 6 instances of prohibition (kinshi), 1 instance of permission (kyoka), and 3 instances of advice (teian). The responses from interlocutors vary between positive and negative responses.